2016
DOI: 10.1002/aic.15413
|View full text |Cite
|
Sign up to set email alerts
|

Computing MOSCED parameters of nonelectrolyte solids with electronic structure methods in SMD and SM8 continuum solvents

Abstract: An efficient method to predict modified separation of cohesive energy density model (MOSCED) parameters for nonelectrolyte solids using electronic structure calculations in SMD and SM8 continuum solvents is proposed and applied to acetanilide, acetaminophen, and phenacetin. The resulting parameters are ultimately used to predict the equilibrium solubility in a range of solvents over a range of temperatures. By combining MOSCED with SMD and SM8, we are able to leverage the strengths of both methods while elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…As might be expected, UNIFAC‐original has a number of advantages over other conventional models since its comprehensive parameter matrix is being obtained from extensive series of VLE and LLE data‐fitted parameters. Nonetheless, interaction parameters are missing for many complex compounds including ionic liquids and dibasic esters, and predictions with existing parameters have shown appreciable error . Recently, to improve the accuracy of phase equilibrium calculations, newly developed equations of state (EOS), such as APACT, SAFT, HM, CPA‐EOS, DFT, and COSMO‐RS, have originated from the statistical fluid theory coupled with quantum chemistry of LLE, wherein efforts are being made to model novel, complex solvent structures …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As might be expected, UNIFAC‐original has a number of advantages over other conventional models since its comprehensive parameter matrix is being obtained from extensive series of VLE and LLE data‐fitted parameters. Nonetheless, interaction parameters are missing for many complex compounds including ionic liquids and dibasic esters, and predictions with existing parameters have shown appreciable error . Recently, to improve the accuracy of phase equilibrium calculations, newly developed equations of state (EOS), such as APACT, SAFT, HM, CPA‐EOS, DFT, and COSMO‐RS, have originated from the statistical fluid theory coupled with quantum chemistry of LLE, wherein efforts are being made to model novel, complex solvent structures …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, interaction parameters are missing for many complex compounds including ionic liquids and dibasic esters, and predictions with existing parameters have shown appreciable error. [26] Recently, to improve the accuracy of phase equilibrium calculations, newly developed equations of state (EOS), such as APACT, SAFT, HM, CPA-EOS, DFT, and COSMO-RS, have originated from the statistical fluid theory coupled with quantum chemistry of LLE, wherein efforts are being made to model novel, complex solvent structures. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] This paper compares the calculations with UNIFAC-original, SERLAS [42,43] (solvation energy relation for liquid associated systems), and modified versions of the latter to give a realistic picture of whether the selected model structure is appropriate for a design application or not.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, ref. 42 suggested that results obtained with MOSCED parameters predicted using solvation free energy calculations with the SMx universal solvent model were superior to predictions made with SMx alone. This may result from implicitly including reference data by using MOSCED parameters that were regressed using reference data.…”
Section: Reference Calculationsmentioning
confidence: 92%
“…At present, MOSCED parameters are available for 130 organic solvents and water [20,74]. Efforts have been made to use electronic structure calculations to predict missing MOSCED parameters, including the use of solvation free energy calculations with the SMx universal solvent models [42,[79][80][81][82][83]. While we would not expect the predicted MOSCED parameters to be as good as those regressed using experimental data, the results of the present study nonetheless would suggest they would yield acceptable results, especially for early stage process conceptualization and design applications.…”
Section: Reference Calculationsmentioning
confidence: 99%
“…The solvation free energy in this context is defined as taking a solute from a non-interacting ideal gas state to solution at the same molecular density (or concentration). We have shown previously that the solvation free energy is readily related to the limiting activity coefficient (γ ∞ i,j ) as [24,[37][38][39][40][41][42]:…”
Section: Methodsmentioning
confidence: 99%